Book Review: The Mystery of the Historical Jesus: The Messiah in the Qur’an, Bible and Historical Sources - Zaid, Omar (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Book Review: The Mystery of the Historical Jesus: The Messiah in the Qur’an, Bible and Historical Sources